Maternal genetic characterization of a Colombian Andean population. Issue 1 (December 2019) - Castillo, A.; Deccache, L.; de Carvalho, E.F.; Simão, F.; Gusmão, L.
Abstract: The development of frequency databases that accurately represent the different populations are of great importance in forensic genetic. This is especially true for South American populations, due to a high genetic diversity and population substructure inside many countries. Concerning Colombian populations, a clear picture of the mtDNA haplotype diversity and its stratification is still lacking. Aiming to fill this gap, samples from individuals living in the Andean region were selected for this study and sequenced for the complete mtDNA control region. Diversity indexes and population comparisons among South American populations were performed. The results showed a high proportion of Native American haplogroups and significant differences among populations from different countries.